Hubungan antara Stres Kerja dengan Aggressive Driving pada Pengemudi Ojek Online di Shelter Stasiun Bekasi - Putri, Yuliana; Widya Nugraha, Andreas Corsini; Arfian Arfian (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Population growth and increased community mobility have contributed to high traffic density in Bekasi, which has also driven the growth of online transportation services such as online motorcycle taxis. Online motorcycle taxi drivers face various work demands, such as income targets, time pressure, and heavy traffic conditions, which can cause job stress and affect their driving behavior. The purpose of this study is to assess the links between job stress and aggressive driving in online motorcycle taxi drivers at the Bekasi Station  Shelter. This study was conducted using a quantitative, correlational design. The study respondents were 107 online motorcycle taxi drivers at the Gojek Shelter at Bekasi Station, selected using total sampling. The research instruments consisted modified of a job stress scale and aggressive driving scale. Data were analyzed using Spearman’s rho correlation. The results indicated a significant positive relationship between job stress and aggressive driving (r = 0.381; p < 0.05). This means that the higher the level of job stress experienced, the greater the tendency for drivers to engage in aggressive driving, and vice versa. These findings may serve as useful input for both companies and online motorcycle taxi drivers in developing strategies and policies to manage stress and ensure driving safety.